Rapid diagnosis of hypoglycin A intoxication in atypical myopathy of horses. (March 2016) - Sander, Johannes; Cavalleri, Jessika-M. V.; Terhardt, Michael; Bochnia, Mandy; Zeyner, Annette; Zuraw, Aleksandra; Sander, Stefanie; Peter, Michael; Janzen, Nils
Hypoglycin A (2-amino-3-(2-methylidenecyclopropyl)propanoic acid) is the plant toxin shown to cause atypical myopathy in horses. It is converted in vivo to methylenecyclopropyl acetic acid, which is transformed to a coenzyme A ester that subsequently blocks beta oxidation of fatty acids. Methylenecyclopropyl acetic acid is also conjugated with carnitine and glycine. Acute atypical myopathy may be diagnosed by quantifying the conjugates of methylenecyclopropyl acetic acid plus a selection of acyl conjugates in urine and serum. We describe a new mass spectrometric method for sample volumes of <0.5 mL. Samples were extracted with methanol containing 5 different internal standards. Extracts were analyzed by ultra–high-performance liquid chromatography–tandem mass spectrometry focusing on 11 metabolites. The total preparation time for a series of 20 samples was 100 min. Instrument run time was 14 min per sample. For the quantification of carnitine and glycine conjugates of methylenecyclopropyl acetic acid in urine, the coefficients of variation for intraday quantification were 2.9% and 3.0%, respectively. The respective values for interday were 9.3% and 8.0%. Methylenecyclopropyl acetyl carnitine was detected as high as 1.18 µmol/L in serum (median: 0.46 µmol/L) and 1.98 mmol/mol creatinine in urine (median: 0.79 mmol/mol creatinine) of diseased horses, while the glycine derivative accumulated up to 1.97 mmol/mol creatinine in urine but was undetectable in most serum samples. In serum samples from horses with atypical myopathy, the intraday coefficients of variation for C4–C8 carnitines and glycines were ≤4.5%. Measured concentrations exceeded those in healthy horses by ~10 to 1, 400 times.